2006
DOI: 10.1136/pgmj.2005.036608
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic findings of an echovirus meningitis outbreak in the north west of England

Abstract: Introduction An outbreak of echovirus meningitis occurred in the north west of England in 2001. This paper reviewed the clinical features and the role of different diagnostic methods. Methods This was a prospective study of adults admitted to a regional infectious disease unit with a probable diagnosis of meningitis, March to August 2001. Results Half the 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
3
24
1
1
Order By: Relevance
“…Although PMN predominance in CSF (Table 2) seems atypical for viral meningitis, previous reports also showed similar result (4,14,21,30 (27). Child-care centers sometimes became the place of outbreaks, but the attack rate ranged from 3 to 13% (23)(24)(25)29).…”
Section: When a Patient With A Possible Diagnosis Of Meningitis Is supporting
confidence: 59%
See 1 more Smart Citation
“…Although PMN predominance in CSF (Table 2) seems atypical for viral meningitis, previous reports also showed similar result (4,14,21,30 (27). Child-care centers sometimes became the place of outbreaks, but the attack rate ranged from 3 to 13% (23)(24)(25)29).…”
Section: When a Patient With A Possible Diagnosis Of Meningitis Is supporting
confidence: 59%
“…were of open community outbreaks (3,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The attack rate was, therefore, quite low.…”
Section: Some Serotypes Have Strong Association With Meningitis Thmentioning
confidence: 99%
“…However, many previous studies of enterovirus meningitis have reported results that contradict this rule (Bernit et al, 2004;Carrol et al, 2006;Kao et al, 2003;Lee & Davies, 2007). Our case series also revealed that 59.7±28.9% of the cells in the cerebrospinal fluid were of polymorphonuclear origin (Table 4).…”
Section: Laboratory Datasupporting
confidence: 49%
“…Echovirus 30 is one of the more common echovirus genotypes; it causes outbreaks every few years, and causes mainly meningoencephalitis in children and adults, with varying clinical severity [20]. Echovirus 13 is a rare genotype that was responsible for major global outbreaks in the early 2000s [18,21].…”
Section: Discussionmentioning
confidence: 99%